Mediações organizacionais e instrumentais em televendas e devoluções de medicamentos - Eva Bessa Soares (2009)
The issue about inefficiency in the instrumental and organizational supports to telemarketing services employees of a pharmacy is the empirical focus of this research. Although whole production process is exposed to failure, the telemarketing services involves the farinteraction between the customer and the seller, cause it more susceptible to failures when it compared to services with face to face contact. In this researched case - telesales of pharmaceutical products - communication problems may occurred between the customer andthe telemarketing operator at the time of information is passing by about the doctor prescription drug resulting in system register failure and, therefore, it back to the company. Internally, the provision of the information by the company to the professionals who have to keep in contact to the customer is another important factor in this kind of business. Since the employee get information by the customer and by the company, the trend to failure can be reduced, since the organization of the attendant services be appropriate in terms of procedure,telemarketing operator qualification, and computing tools and systems. The used approach was the EAW methodology (Ergonomic Analysis of Work) for work conditions analysis at the telemarketing salesman, then the collected data were analyzed based at some theories of human error, especially Norman (1981, 1983, 1988, 1991 e 1994), Reason (1987, 1993, 2000 e 2002), Amalberti (1996) and Clot (2006). The resulting showed that materials and organizational conditions have some aspects make harder the job execution and influence the products devolution. The thesis defended here is that the faults that result in devolutions ofpharmaceutical products happen of the interaction of the worker with its context of work. They cannot be considered consequences of attention lack or as guilt of the telemarketing operators; therefore the cognitive process does not happen only in the mind of these workers. It also occurs in the relations of the worker with the way. Under this view the faults was result of the interaction of many factors such as the inefficiency of instrumental support (software, head-set and computers) and organizational (supervisor, coordinators and pharmaceutical). Those inadequacies of the context result in difficulties for them to manage the own cognitive processes, mainly the attention and the memory, could cause failure in the system registrations of the customers requests.